2018
DOI: 10.1186/s41239-018-0116-z
|View full text |Cite
|
Sign up to set email alerts
|

The utilisation of e-learning facilities in the educational delivery system of Nigeria: a study of M-University

Abstract: In spite of the constant innovative approaches adopted by teachers in western world, traditional approaches to teaching and assessments in Nigeria tertiary institutions have constantly been practiced. Most institutions are not able to fully utilize e-learning or get full advantages of it. This failure has hindered most teachers in using innovative teaching methodologies in delivering their lectures, and undertake rigorous research works. The study examines adoption and utilisation of elearning facilities by le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
148
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(166 citation statements)
references
References 28 publications
(39 reference statements)
11
148
3
4
Order By: Relevance
“…Another finding revealed that there was no significant difference in the utilization of E-learning facilities for teaching physics based on teachers' teaching experience. This was in contrary to the finding of Eze, et al [15] who found out that teachers with less experience utilize E-learning facilities in their teaching more than teachers with more experience. This might be that teachers with less experience spend more of their time in utilizing E-learning facilities.…”
Section: Hypotheses Testingcontrasting
confidence: 94%
See 1 more Smart Citation
“…Another finding revealed that there was no significant difference in the utilization of E-learning facilities for teaching physics based on teachers' teaching experience. This was in contrary to the finding of Eze, et al [15] who found out that teachers with less experience utilize E-learning facilities in their teaching more than teachers with more experience. This might be that teachers with less experience spend more of their time in utilizing E-learning facilities.…”
Section: Hypotheses Testingcontrasting
confidence: 94%
“…Teachers with 16 to 20 years of experience were found to have a higher utilization level of Elearning facilities than those between 11 and 15 years while teachers having teaching experience between 6 and 10 years were found to have a higher utilization level of E-learning facilities than those between 1 and 5 years. Eze, et al [15] opined that teachers with less experience in teaching utilizes E-learning facilities in their teaching more than teachers with more experience in teaching.…”
Section: Introductionmentioning
confidence: 99%
“…The e-learning experiences of students in higher education institutions tend to be integrated with academic experiences for sustainable learning improvement because they are relevant not only to academic success but also to lifelong learning for personal success. The e-learning environment in a higher education institution is a learning ecosystem that integrates digital technology with teaching and learning practices as a significant educational innovation, by advancing technology-enabled platforms (Eze, Chinedu-Eze, & Bello, 2018). The benefits of e-learning environments for students and universities are saving substantial costs for physical teaching and learning infrastructure, contributing to the digitization of course contents to easily share and adopt learning contents anytime and anywhere, and integrating the global educational environment (Pham, Limbu, Bui, Nguyen, & Pham, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve a high rate of student academic success, e-learning in higher education encompasses the use of digital technologies to build educational materials for teaching and learning, to teach learners, and to regulate courses (Fry, 2001;Parkes et al, 2015). E-learning has expanded rapidly with the popularization and advancement of multimedia and network technologies such as high-speed Internet, high-definition video, smart devices, and intelligent functionalities of learning management systems (Cidral, Oliveira, Di Felice, & Aparicio, 2018;Eze et al, 2018). Advances in e-learning environments at universities around the world continue to contribute to improving students' academic success (Castillo-Merino & Serradell-López, 2014;Naveed, Muhammed, Sanober, Qureshi, & Shah, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, primary, secondary and tertiary institutions in Nigeria are still closed and this has seriously affected millions of students in tertiary institutions who have their semesters cancelled or suspended due to the pandemic. While many other countries have switched to virtual learning, many tertiary institutions within Nigeria lack the various online educational platforms or facilities for such method of teaching (Eze et al, 2018), which could worsen the situation for students in the country. Several studies have reported students' mental health becomes greatly affected when faced with a public health emergency and academic delays, which has been positively correlated with anxiety levels (Pragholapati, 2020., Huang et al, 2020Duong et al, 2020;Werner et al, 2020;Roy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%